Influence of microalgae on the microbial composition of fishery wastewater (Experimental biology, 2020)
The article presents the results of a study that examined the effect of the green microalgae strain Chlorella vulgaris Z-1 on the sanitary-microbiological state of wastewater from trout and sturgeon ponds of the Saymasay fishery. The wastewater of both ponds of fisheries was characterized by a high content of organo-mineral substances. According to the results of sanitary-bacteriological studies, the total microbial number (TMN) of water in the ponds amounted to 5,6- 6,4x 105KOE / cm3 of water, at the water quality index of 10, and the presence of aeromonads and pseudomonads was also noted. It was found that after the cultivation of the microalgae Chl vulgaris Z-1 in the wastewater of the sturgeon and trout pond, the microbiological characteristic improved significantly, the TMN decreased by 70-75%, and the water of the Saymasay fishery, with index 5, considered to be clean by evaluating the degree of pollution. It was found in the morphological composition of the microflora of both ponds that there was a noticeable decrease in the groups of rod-shaped microorganisms, an increase in the content of cocciform bacteria and the absence of aeromonads and pseudomonads. A change in the ratio of physiological groups of microorganisms in purified water after microalgae cultivation was revealed. The number of ammonifying and denitrifying bacteria noticeably decreased, while the number of nitrifying microorganisms increased significantly, which indicates the content of semi-decomposed organic residues involved in the ammonification process.Key words: Chlorella vulgaris Z-1, TMN (total microbial number), sanitary and microbiological condition, fishery waste water.